(untitled) (International journal of medical sciences, 2026)
Ischemic stroke is a leading cause of mortality and long-term disability worldwide. Early diagnosis and timely management are essential to reduce infarct size, preserve neurological function, and improve patient outcomes. This review discusses advances in early detection using neuroimaging, thrombolytic therapy, endovascular interventions, neuroprotective strategies, and multidisciplinary rehabilitation. Evidence from recent clinical trials demonstrates that prompt treatment significantly enhances functional recovery and reduces complications. Secondary prevention measures, including antiplatelet therapy, anticoagulation, and lifestyle modification, are critical for reducing recurrence. Integration of rapid diagnostic techniques, evidence-based therapeutic approaches, and structured rehabilitation forms a comprehensive strategy for managing ischemic stroke. Continuous research and standardized clinical protocols are essential for improving prognosis and quality of life in affected patients.